Short-term impacts of oil spills on fungal population of beach soil in Botongon, Estancia, Iloilo, Philippines. - Ip, Kenji O.
The continued dependence on oil has resulted to numerous oil spills globally. Such events bring about changes or disturbances on sensitive coastal habitats on both short and long term periods. Recently, another major oil spill occurred in the Philippines, specifically at Estancia, Iloilo on November 9, 2014, due to damage of Napocor Power barge 103. When Typhoon Yolanda made a landfall in northern Iloilo on Novemebr 8, 2013, the power barge was dislodged from its moorings and then slammed onto the rocky shoreline of barangay Botongon. The oil spilled contaminated the coastlines of the Estancia, Batad and portions of San Dionisio and Concepcion. A total of 893,920 liters was spilled from 1,448,570 liters load before Typhoon Yolanda hit. Studies on the impacts of oil spills on fungal population in the tropics is wanting. While initial published reports from other sites indicate a change on fungal density and assemblage has been noted on a short-term, much work is needed if similar observations will apply in other oil impacted sites. Thus, the need for the present study. This study aimed to: 1. describe, identify and classify fungi collected; 2) describe the fungal population in terms of: a) Species frequency of occurrence per site, b)Total frequency of occurrence per site, c)Shannon index of diversity and evenness; and d) Compare Jaccard's index of similarity of fungal population among sites. Beach soil samples were collected on January 11, 2014 at barangay Botongon, Estancia, Iloilo. Fungi were enumerated and isolated using the spread plate serial dilution technique and identified based on colony and microscopic characteristics using available keys and monographs. In general, fungal density was higher at oiled sites compared with un-oiled site and there was a dominance of members of the hypgomycetes on both sites. A total of 7 species, Aspergillus flavipes, A. niger, A. paraciticus, Hyphomycete 1, Monilia sitophila, Mycelia sterilia, Penicillum corylophilum, were found in oiled sites with a density of 5.77 x10 raised to the fourth power CFU/g and only 4 species, aspegillus niger, A. paraciticus, Monilia sitophila, Penicilliumcorylophilum, were present in the unoiled site with a lower density of 2.45 x 10 raised to the 4th power CFU/g. The observed diffrence in fungal population and density could possibly be attributed to the oiled spilled in the areas. This report further confirms the other observations on the impacts of oil on fungal population in a tropical setting on a short-term basis.